Salamon syndrome. - Kiss, P.; Török, É. (European Journal of Pediatric Dermatology, 2018)
Salamon syndrome is a rare and unique dysmorphia syndrome with recessive inheritance. Woolly hair, hypotrichosis and profound mental retardation are the characteristic features of this condition. Two unrelated girls are presented, showing all the typical features of the syndrome.